2017
DOI: 10.1097/shk.0000000000000713
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Improves Incidence and Severity of Necrotizing Enterocolitis by Lymphocyte Balance Restitution and Repopulation of LGR5+ Intestinal Stem Cells

Abstract: Necrotizing enterocolitis (NEC) is the most devastating gastrointestinal disease of the premature infant. We have recently shown that NEC development occurs after an increase in proinflammatory CD4+Th17 (Th17) cells and reduced anti-inflammatory Foxp3+ regulatory T cells (Tregs) to the premature small intestine of mice and humans, which can be experimentally reversed in mice by administration of all-trans retinoic acid (ATRA). We have also shown that NEC is characterized by apoptosis of Lgr5-positive intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…3a), suggesting that the intestinal stem cells (ISCs) in the intestinal crypts were severely damaged. This finding was consistent with a report by Nino et al 19 showing that NEC is characterized by apoptosis of intestinal stem cells located at the bottom of the intestinal crypts. Compared to the NEC injury group, the degree of apoptosis in the small intestine epithelium 1, 4, and 7 days after the PHDMSC-CM treatment was significantly reduced in the NEC model.…”
Section: Phdmsc-cm Reduced Apoptosis Of the Intestinal Epithelial Celsupporting
confidence: 94%
See 1 more Smart Citation
“…3a), suggesting that the intestinal stem cells (ISCs) in the intestinal crypts were severely damaged. This finding was consistent with a report by Nino et al 19 showing that NEC is characterized by apoptosis of intestinal stem cells located at the bottom of the intestinal crypts. Compared to the NEC injury group, the degree of apoptosis in the small intestine epithelium 1, 4, and 7 days after the PHDMSC-CM treatment was significantly reduced in the NEC model.…”
Section: Phdmsc-cm Reduced Apoptosis Of the Intestinal Epithelial Celsupporting
confidence: 94%
“…Lgr5expressing cells are actively proliferating ISCs responsible for the maintenance of the intestinal epithelium. The loss of Lgr5 + ISC pools has been implicated in NEC pathophysiology as it can cause decreased capacity for intestinal epithelial tissue regeneration and renewal that is observed in NEC 19 . In this study, expression of the Lgr5 + ISCs was very scattered 3 days after the NEC injury, with only 1-2 Lgr5-positive cells located at the very bottom of the intestinal crypt.…”
Section: Phdmsc-cm Promoted Intestinal Epithelial Stem Cell Regeneratmentioning
confidence: 99%
“…By upregulating signal transducer and activator of transcription 3, TLR4 promoted the polarization of T cells toward CD3 + CD4 + IL-17 + profile, whereas it reduced Foxp3 + regulatory T cells (20). This finding had been observed both in enterocytes and Lgr5 + intestinal stem cells (21). Our study observed elevated expression of proinflammatory cytokines in NEC, including IL-17, that could be ameliorated by vitamin D. There might be several pathways leading to this change and inhibition of TLR4 should be one of them.…”
Section: Discussionmentioning
confidence: 88%
“…There might be other mechanisms of the intestinal-protective effect of vitamin D in NEC. Immunological disturbance was an important pathological basis for NEC (21,23), and vitamin D had long been regarded as an important immunological regulator. Thus, there was reason to believe that immunological regulation was possibly another way by which vitamin D suppressed NEC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Th17 cells, characterized by production of the inflammatory interleukin 17A (IL-17A) cytokine, have been shown to be upregulated in both murine and human NEC, and are thought to play a role in intestinal barrier dysfunction [34]. In an experimental model of NEC, mice treated with all-trans retinoic acid (ATRA), an inhibitor of Th17 differentiation [78], showed lower levels of Th17 cells, increased populations of Tregs, and reduced NEC severity [34,79]. Interestingly, retinoic acid is produced endogenously by IECs, but this production is thought to be largely dictated by luminal commensal bacteria [80].…”
Section: Adaptive Immune Systemmentioning
confidence: 99%